Front cover: Absorption, distribution, metabolism, and excretion of [14C]sesamin in rats. Issue 8 (August 2017) - Tomimori, Namino; Rogi, Tomohiro; Shibata, Hiroshi
Abstract : Mol. Nutr. Food Res. 2017, 61, 1600844. DOI:10.1002/mnfr.201600844 Sesamin is a major lignan in sesame seeds and has various physiological effects. Sesamin is absorbed efficiently and distributed over the whole body. In particular, it is highly distributed in the form of its metabolites in the liver and kidney. The various physiological effects of sesamin may be due to the action of its metabolites.